PENGEMBANGAN KURIKULUM PROGRAM KETERAMPILAN LIFE SKILL DI MADRASAH ALIYAH NEGERI 1 SRAGEN - Achfan Aziz Zulfandika; Saiddaeni Saiddaeni (PASCASARJANA UNISNU, 2023)
AbstractBased on the Decree of the Director General Number 4924 of 2016 and Number 2851 of 2020, regarding the implementation of skills programs stipulated by the ministry of religion. The development of the life skill Madrasah Aliyah Negeri 1 Sragen as an actualization equips students to have skills as life support when they are in the community. This study aims to find out how the curriculum development of life skills program is implemented by Madrasah Aliyah Negeri 1 Sragen. The curriculum implemented by the institution uses the Education Unit Level Curriculum (KTSP). This research method uses a qualitative approach with a structured and empirical type of exploration with interview techniques, observation, and documentation studies. The analysis technique includes three processes, namely data reduction, data exposure, and drawing conclusions. The results of the study can be drawn conclusions 1) The life skills are given in intra-curricular learning and must be followed by all students, except for digital classes. 2) The development process implemented in general is good. 3) The Life Skills that are applied are eight mandatory programs and four new programs. It is better for institutions to carry out life skills funding separately.Keywords: Curriculum Development; Life Skill; MadrasahAbstrakBerlandaskan SK Dirjen Nomor 4924 Tahun 2016 dan Nomor 2851 Tahun 2020, tentang pelaksanaan program keterampilan yang ditetapkan oleh kementrian agama. Pengembangan program life skill Madrasah Aliyah Negeri 1 Sragen sebagai aktualisasi membekali peserta didik untuk memiliki kecakapan sebagai penunjang kehidupan saat berada di lingkungan masyarakat. Penelitian ini bertujuan untuk mengetahui bagaimana pengembangan kurikulum program keterampilan life skill yang dilaksanakan Madrasah Aliyah Negeri 1 Sragen. Kurikulum yang diterapkan lembaga menggunakan Kurikulum Tingkat Satuan Pendidikan (KTSP). Metode penelitian ini menggunakan pendekatan kualitatif jenis eksplorasi terstruktur dan empiris dengan teknik wawancara, observasi, dan studi dokumentasi. Teknik analisis mencakup tiga proses yaitu reduksi data, paparan data, dan penarikan kesimpulan. Hasil penelitian dapat ditarik kesimpulan 1) Program life skill diberikan dalam pembelajaran intrakulikuler dan wajib diikuti semua peserta didik, terkecuali kelas digital. 2) Proses pengembangan yang dilaksanakan secara umum bagus. 3) Life Skil yang diterapkan terdapat delapan program wajib dan empat program baru. Sebaiknya lembaga melaksanakan pendanaan life skill secara terpisah.Kata kunci: Life Skill; Madrasah; Pengembangan Kurikulum